Base metal plating film
Patent Information
- Application Number
- JP2020530202
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-22
- Filing Date
- 2019-07-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-07-09
AI Technical Summary
【0018】 本発明の卑金属めっき膜は、ナノダイヤモンド粒子が卑金属のマトリックス中に高分散した構成を有し、前記ナノダイヤモンド粒子によって卑金属の結晶の成長が阻害されて結晶粒が微細化するためか、表面が平滑化され、高い光沢度と優れた耐酸化性を有する。また、本発明の卑金属めっき膜は優れた耐熱性、表面硬度、導電率を有する。そのため、本発明の卑金属めっき膜は電子機器用接続部品や装飾品等に好適に用いられる。
Smart Images

Figure 0007638706000012 
Figure 0007638706000013 
Figure 0007638706000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a base metal plating film, a base metal plating bath, a method for producing the base metal plating film, an electronic component provided with the base metal plating film, a brightener for the base metal plating film, and an antioxidant for the base metal plating film.
[0002] In this specification, "nanodiamond" may be abbreviated as "ND." [Background technology]
[0003] Among the connection parts used in electric and electronic equipment, such as low-current (signal system) switches and connectors, connection parts that are used repeatedly under low contact load require high connection reliability, and therefore connection parts in which the surface of conductive metal members is plated with metals such as precious metals are used as such connection parts. In addition to being conductive, the plating film may be required to have a suitable gloss.
[0004] Patent Document 1 discloses a method for preparing a plating bath in which carbon nanotubes or other carbon-based particles are dispersed in a non-aqueous solvent, and then the non-aqueous solvent is added to an aqueous metal salt solution containing base metal ions such as copper ions and the solution is stirred to disperse the carbon-based particles in the aqueous base metal salt solution, in order to obtain a high-quality, highly reliable plating film that is composited with carbon-based particles. It is said that the use of the plating bath prepared by this method makes it possible to obtain electronic components with reduced inclusion of impurities. However, this method cannot impart high gloss to the plating film. In addition, base metals are easily oxidized by air.
[0005] One method for imparting gloss to a plating film is to add a brightener to the plating bath. The brightener has the effect of micronizing the crystals by adsorbing to the crystal nuclei and inhibiting their growth, thereby smoothing the surface of the deposited precious metal and making it glossy (see, for example, Patent Document 2).
[0006] Non-Patent Document 1 proposes adding nanodiamond particles to a plating bath to incorporate the nanodiamond particles into the plating film, but it describes that the nanodiamond particles are not sufficiently dispersed in the plating solution, and therefore the nanodiamond particles in the plating bath are aggregated to the order of μm.
[0007] Patent Document 3 describes a configuration in which a hydrophilic polymer or diamond microparticles into which ionic functional groups have been introduced are added together with a surfactant to a metal plating solution, and describes a configuration in which a dispersion containing 1 g / L of diamond microparticles into which anionic functional groups have been introduced is added at a rate of 2 g / L in Example 1, and a dispersion containing 1 g / L of diamond microparticles into which PEG has been introduced is added at a rate of 0.1 g / L in Example 2. However, with these addition amounts, improvements in the gloss and oxidation resistance of the plating film cannot be expected.
[0008] Patent Document 4 describes a configuration in which diamond microparticles with an average particle size of 10 nm to 300 nm and having hydrophilic polymers or ionic functional groups introduced therein, fluororesin microparticles with an average particle size of 100 nm to 300 nm, and a surfactant are added to a metal plating solution, and in Examples 1 and 2, an electroless composite plating solution containing 2.0 g / L of grafted diamond microparticles is described. However, with a plating solution containing such a high concentration of diamond microparticles, improvements in the gloss and oxidation resistance of the plating film cannot be expected. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO2011 / 048984 [Patent Document 2] JP 2015-117424 A [Patent Document 3] JP 2011-149071 A [Patent Document 4] JP 2012-092416 A [Non-patent literature]
[0010] [Non-Patent Document 1] Hiroshi Matsubara “Surface Technology” Vol.65, No.2, (2014), pp. 88-93 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a base metal plating film having high gloss and oxidation resistance, and a method for producing the same.
[0012] Another object of the present invention is to provide a base metal plating bath which is useful for producing a base metal plating film having high gloss and oxidation resistance.
[0013] Another object of the present invention is to provide an electronic component having a base metal plating film having high gloss, surface hardness, electrical conductivity and oxidation resistance.
[0014] Another object of the present invention is to provide a novel brightener which imparts high brightness to a base metal plating film.
[0015] Another object of the present invention is to provide a novel antioxidant which imparts oxidation resistance to base metal plating films. [Means for solving the problem]
[0016] As a result of intensive research to solve the above-mentioned problems, the inventors have discovered that when base metal plating is performed using a plating bath containing base metal ions and to which hydrophilic nanodiamond particles have been added, a base metal plating film having high gloss and excellent oxidation resistance can be obtained.
[0017] The present invention provides the following base metal plating film, a base metal plating bath, a method for producing the base metal plating film, an electronic component provided with the base metal plating film, a brightener for the base metal plating film, and an antioxidant for the base metal plating film. [1] A base metal plating film comprising a base metal matrix and hydrophilic nanodiamond particles dispersed in the base metal matrix. [2] The base metal plating film described in [1] has a glossiness at an incident angle of 60° that is 10 or more higher than that of the same base metal plating film as described above except that it does not contain the hydrophilic nanodiamond particles. [3] The base metal plating film according to [1] or [2], wherein after storage for 7 days at 25°C and 50% humidity in a room away from direct sunlight, the increase in base metal oxide content of the base metal plating film immediately after production is less than 1%, preferably less than 0.5%, more preferably less than 0.3%, and most preferably less than 0.1%. [4] The base metal plating film according to any one of [1] to [3], which is free of a surfactant. [5] The base metal plating film according to any one of [1] to [4], wherein the hydrophilic nanodiamond particles are nanodiamond particles of the following (i) or (ii): (i) Nanodiamond particles coated with hydrophilic polymer; (ii) Nanodiamond particles modified with hydrophilic polymers. [6] The plating film according to any one of [1] to [5], wherein the base metal is at least one selected from the group consisting of iron, nickel, zinc, copper, tin, aluminum, tungsten, molybdenum, tantalum, magnesium, cobalt, bismuth, cadmium, titanium, zirconium, antimony, manganese, beryllium, chromium, germanium, vanadium, gallium, hafnium, indium, niobium, permalloy, rhenium, and thallium. [7] The base metal plating film described in any one of [1] to [6], wherein the average particle diameter (D50) of the hydrophilic nanodiamond particles dispersed in the base metal matrix is in the range of 4 to 95 nm as measured by SEM method. [8] The base metal plating film according to [5], wherein the hydrophilic polymer is selected from the group consisting of polyglycerin, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, poly(meth)acrylic acid, polyacrylamide, polyethyleneimine, vinyl ether polymers, cellulose derivatives, water-soluble polyesters, water-soluble phenolic resins, and natural polymer polysaccharides. [9] The base metal plating film according to any one of [1] to [8], wherein the base metal is copper, the crystallite size (A) of the 111 plane is 100 nm or less, the crystallite size (B) of the 220 plane is 80 nm or less, and the crystallite size ratio (A / B) of the 111 plane to the 220 plane is 1.3 or more.
[10] The base metal plating film according to any one of [1] to [8], wherein the base metal is copper, and the peak intensity ratio of the 111 plane to the 220 plane (111 plane / 220 plane) in an X-ray diffraction pattern is 3.0 or less.
[11] The base metal plating film according to any one of [1] to [8], wherein the base metal is nickel, the crystallite size (A) of the 111 plane is 25 nm or less, the crystallite size (C) of the 200 plane is 23 nm or less, and the crystallite size ratio (A / C) of the 111 plane to the 200 plane is 1.1 or more.
[12] A base metal plating bath comprising base metal ions and hydrophilic nanodiamond particles, the concentration of the hydrophilic nanodiamond particles being 0.001 to 1 g / L.
[13] The base metal plating bath according to
[12] , having a haze of 0 to 0.5.
[14] The base metal plating bath according to
[12] or
[13] , wherein the particle size (D10) of the hydrophilic nanodiamond particles in the base metal plating bath is 10 to 60 nm.
[15] The base metal plating bath according to
[12] or
[13] , wherein the particle size (D50) of the hydrophilic nanodiamond particles in the base metal plating bath is 10 to 70 nm.
[16] The base metal plating bath according to
[12] or
[13] , wherein the particle size (D90) of the hydrophilic nanodiamond particles in the base metal plating bath is 10 to 90 nm.
[17] A method for producing a plating film described in any one of [1] to
[11] , characterized in that a specimen is immersed in a base metal plating bath containing base metal ions and hydrophilic nanodiamond particles, and in which the concentration of the nanodiamond particles is 0.001 to 1 g / L, and electrolytic plating is performed.
[18] The method for producing a plating film according to
[17] , wherein the haze of the base metal plating bath is 0 to 0.5.
[19] An electronic component comprising the plating film according to any one of [1] to
[11] .
[20] A brightener for base metal plating containing hydrophilic nanodiamond particles. [twenty one] An antioxidant for base metal plating films containing hydrophilic nanodiamond particles. Effect of the Invention
[0018] The base metal plating film of the present invention has a structure in which nanodiamond particles are highly dispersed in a base metal matrix, and the nanodiamond particles inhibit the growth of base metal crystals, resulting in finer crystal grains, which results in a smooth surface, high gloss, and excellent oxidation resistance. The base metal plating film of the present invention also has excellent heat resistance, surface hardness, and electrical conductivity. Therefore, the base metal plating film of the present invention is suitable for use in electronic device connection parts, decorative items, and the like.
[0019] In addition, the base metal plating film of the present invention has a smooth surface, which reduces the coefficient of friction and the contact resistance, making it suitable for use in connection parts (or electrical contacts) such as low-current (signal system) switches and connectors used in electric and electronic devices that are used repeatedly under low contact loads.
[0020] The plating bath of the present invention is useful for producing a base metal plating film having high gloss and excellent oxidation resistance.
[0021] According to the method for producing a base metal plating film of the present invention, a base metal plating film having high gloss and excellent oxidation resistance can be produced efficiently by simple operations.
[0022] The electronic component of the present invention has a base metal plating film with high gloss and excellent oxidation resistance.
[0023] The brightener of the present invention is useful for forming a base metal plating film having high gloss.
[0024] The antioxidant of the present invention is useful for forming a base metal plating film having excellent oxidation resistance. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is an enlarged schematic view showing an example of a hydrophilic ND particle in the present invention. [Diagram 2] 1 shows the results of X-ray diffraction of the plating film formed on the brass plate in Comparative Example 1. [Diagram 3] 1 shows the results of X-ray diffraction of the plating film formed on the brass plate in Example 4. [Figure 4] 1 shows the X-ray diffraction results of the plating film formed on the brass plate in Comparative Example 2 immediately after production and 5 days after production. [Diagram 5] 1 shows an XRD pattern of the copper plating film measured in Test Example 7. [Figure 6] 13 shows SEM photographs of the plating film of Test Example 8. (a) without ND, (b) with ND. [Figure 7] C1s (XPS) in the copper plating film obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] [Hydrophilic ND particles] The ND particles used in the present invention are hydrophilic ND particles, which are (i) ND particles coated with a hydrophilic polymer, and (ii) ND particles modified with hydrophilic polymers The preferred hydrophilic ND particles are the ND particles of (ii).
[0027] ND particles to which hydrophilic functional groups (OH, COOH, NH2) have been introduced are known (e.g., JP 2018-30741 A), and for example, ND produced by the detonation method can be preferably used. The detonation method includes the air-cooled detonation method and the water-cooled detonation method. In the present invention, the air-cooled detonation method is particularly preferred since it can obtain NDs with smaller primary particles than the water-cooled detonation method. By performing the detonation under an air atmosphere or a nitrogen atmosphere, hydrophilic ND particles having multiple hydrophilic functional groups (OH, COOH, NH2) formed on the surface can be obtained. Coating or modification with a hydrophilic polymer is performed via the hydrophilic functional group.
[0028] Examples of hydrophilic polymers include polyglycerin (PG), polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, poly(meth)acrylic acid, polyacrylamide, polyethyleneimine, vinyl ether polymers, cellulose derivatives, water-soluble polyesters, and natural polymer polysaccharides. Examples of vinyl ether polymers include homopolymers or copolymers of alkyl vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, vinyl isopropyl ether, vinyl butyl ether, and vinyl isobutyl ether (e.g., polyvinyl methyl ether, polyvinyl ethyl ether, and vinyl ether-maleic anhydride copolymers). Examples of cellulose derivatives include methyl cellulose, ethyl cellulose, propyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and carboxyethyl cellulose. Examples of water-soluble polyesters include polydimethylolpropionic acid esters. Examples of natural polymer polysaccharides include alginic acid or its salts, pectin, starch, agar, gum arabic, dextrin, and carrageenan. Preferred hydrophilic polymers are polyglycerin, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, and poly(meth)acrylic acid, with polyglycerin being particularly preferred.
[0029] An ND particle modified with a surface modifying group containing a polyglycerin chain has a structure in which, for example, polyglycerin represented by the following formula (1) is bonded to a surface functional group of the ND particle, where n represents the number of glycerin units constituting the polyglycerin chain and is an integer of 1 or more.
[0030] HO-(C3H6O2) n -H (1) The C3H6O2 in the parentheses of formula (1) has a structure represented by the following formula (2) and / or (3).
[0031] -CH2-CHOH-CH2O- (2) -CH(CHOH)CHO- (3) The polyglycerol chain includes polyglycerol chains of a linear structure, a branched structure, and a cyclic structure.
[0032] The amount of the hydrophilic polymer introduced by modification or coating is, for example, about 0.05 to 1.0 part by mass, preferably about 0.4 to 1.0 part by mass, more preferably 0.5 to 0.9 parts by mass, and particularly preferably 0.6 to 0.8 parts by mass, per part by mass of the ND particle portion. If the amount of the hydrophilic polymer introduced is within the above range, aggregation of the ND particles can be prevented. The mass ratio of the hydrophilic polymer portion to the ND particle portion can be determined by measuring the change in mass during heat treatment using a differential thermogravimetry analyzer (TG-DTA) or the composition ratio by elemental analysis.
[0033] Coating of ND particles with hydrophilic polymers can be achieved by contacting nanodiamond particles with a hydrophilic polymer solution and then centrifuging the solution to separate the hydrophilic polymer that is not involved in the coating, and collecting the nanodiamond particles coated with the hydrophilic polymer.
[0034] The modification of ND particles with hydrophilic polymers can be carried out by using the ND particles having hydrophilic functional groups (OH, COOH, NH2, etc.) introduced on the surface as a raw material, and binding a hydrophilic polymer group to the hydrophilic functional group via a linker group such as an ester bond, an amide bond, an imide bond, an ether bond, a urethane bond, or a urea bond. The linker group can be formed by a method of forming an ester or amide bond using a condensing agent such as dicyclohexylcarbodiimide, a water-soluble carbodiimide, or a carbonyldiimidazole, a method of forming a urethane bond or a urea bond using a hydrophilic polymer having an isocyanate group (N=C=O), or, when the hydrophilic polymer has a COOH group, a method of converting the COOH group to an acid halide (particularly an acid chloride) or an acid anhydride, and reacting the converted group with an ND particle having an OH or NH2 group to form an ester bond or an amide bond.
[0035] The ND particles having hydrophilic functional groups (OH, COOH, NH2) introduced therein and used as a raw material for coating with or modifying with a hydrophilic polymer are preferably fine particles having an average primary particle size of 10 nm or less, for example, 1 to 10 nm.
[0036] The hydrophilic ND particles of the present invention are preferably fine particles having an average primary particle size of 12 nm or less, for example, 1 to 12 nm, and preferably 3 to 12 nm.
[0037] The average particle size of the primary particles of ND particles having hydrophilic functional groups and ND particles coated or modified with hydrophilic polymers was measured by small angle X-ray scattering (SAXS method) using an X-ray diffraction device (product name "S smart Lab", manufactured by Rigaku Corporation), and the nanodiamond primary particles were determined to be spherical and have a particle density of 3.51 g / cm using particle size distribution analysis software (product name "NANO-Solver", manufactured by Rigaku Corporation). 3 This can be determined by estimating the primary particle size of nanodiamonds in the scattering angle range of 1° to 3°, assuming that the scattering angle is 1° to 3°.
[0038] The hydrophilic ND particles are preferably fine particles having an average primary particle size of 10 nm or less, for example, 1 to 10 nm.
[0039] By making the surface of ND particles hydrophilic, aggregation can be prevented, and glossiness and oxidation resistance can be improved at the same time. On the other hand, ND particles such as those described in Non-Patent Document 1, in which no hydrophilic functional group or hydrophilic polymer is introduced, do not improve glossiness and oxidation resistance even when introduced into a base metal plating film. As described in Test Example 2 of this specification, the average particle size of the primary particles of ND obtained by the detonation method is 10 nm or less, but the particle size of the primary particles of ND obtained by the shock compression method is much greater than 10 nm, so ND particles produced by the detonation method are preferred. In the present invention, it is not necessary to add a surfactant to the base metal plating bath. If the plating bath contains a surfactant, even a small amount of the surfactant may be incorporated into the base metal plating film, so it is preferable not to use a surfactant. In addition, it is preferable that the base metal plating film is surfactant-free.
[0040] [Base metal plating film] The base metal plating film of the present invention is a base metal plating film containing a base metal matrix and hydrophilic ND particles dispersed in the base metal matrix. In a preferred embodiment of the present invention, the hydrophilic ND particles may be uniformly dispersed in the base metal matrix, or may be densely dispersed near the surface of the base metal matrix.
[0041] The base metal includes at least one selected from the group consisting of iron, nickel, zinc, copper, tin, aluminum, tungsten, molybdenum, tantalum, magnesium, cobalt, bismuth, cadmium, titanium, zirconium, antimony, manganese, beryllium, chromium, germanium, vanadium, gallium, hafnium, indium, niobium, rhenium, and thallium, and is preferably at least one selected from the group consisting of copper, nickel, zinc, tin, chromium, and permalloy, and more preferably at least one selected from the group consisting of copper, nickel, zinc, and tin.
[0042] A base metal plating film according to a preferred embodiment of the present invention is a base metal plating film including a base metal matrix and hydrophilic ND particles dispersed in the base metal matrix, and is characterized in that the glossiness at an incident angle of 60° is 770 or more. In addition, in the case of 100% reflection, the glossiness is 1000.
[0043] The gloss of the base metal plating film of the present invention at an incidence angle of 60° is 770 or more, preferably 780 or more, more preferably 800 or more, and even more preferably 850 or more, when the base metal is copper.
[0044] The gloss of the base metal plating film of the present invention at an incidence angle of 60° is 560 or more when the base metal is nickel, 785 or more when the base metal is tin, 575 or more when the base metal is permalloy, and 410 or more when the base metal is zinc.
[0045] Furthermore, compared to a base metal plating film of the same composition as the present invention except that it does not contain hydrophilic ND particles, the gloss of the base metal plating film of the present invention at an incident angle of 60° is, for example, 10 or more (e.g., 10 to 200) higher, preferably 15 or more higher, more preferably 35 or more higher, particularly preferably 55 or more higher, and most preferably 85 or more higher.
[0046] The base metal plating film of the present invention preferably exhibits an increase in base metal oxide of less than 1%, more preferably less than 0.5%, even more preferably less than 0.3%, and most preferably less than 0.1% after storage for 7 days at room temperature (around 25°C, humidity of about 50%) away from direct sunlight, compared to the base metal plating film immediately after production.
[0047] The surface roughness (Ra) of the base metal plating film of the present invention is, for example, 0.5 μm or less, preferably 0.4 μm or less, more preferably 0.3 μm or less, particularly preferably 0.15 μm or less, and most preferably 0.1 μm or less.
[0048] In the base metal plating film of the present invention, the particle size of the hydrophilic ND particles dispersed in the base metal matrix, as measured by SEM, is, for example, in the range of 4 to 95 nm, preferably 10 to 80 nm, particularly preferably 20 to 60 nm, and most preferably 30 to 50 nm.
[0049] In one preferred embodiment of the present invention, when the base metal is copper, the crystallite size (A) of the 111 plane is 100 nm or less, preferably 80 nm or less, more preferably 70 nm or less, even more preferably 60 nm or less, particularly preferably 50 nm or less, and most preferably 45 nm or less, and the crystallite size (B) of the 220 plane is 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, even more preferably 40 nm or less, particularly preferably 35 nm or less, and most preferably 30 nm or less. The crystallite size ratio (A / B) of the 111 plane to the 220 plane is preferably 1.3 or more, more preferably 1.3 to 1.6.
[0050] In one preferred embodiment of the present invention, when the base metal is nickel, the crystallite size (A) of the 111 plane is 25 nm or less, preferably 24 nm or less, more preferably 23 nm or less, and even more preferably 22 nm or less, and the crystallite size (C) of the 200 plane is 23 nm or less, preferably 20 nm or less, more preferably 18 nm or less, even more preferably 16 nm or less, and particularly preferably 14 nm or less. The crystallite size ratio (A / C) of the 111 plane to the 200 plane is preferably 1.1 or more, and more preferably 1.1 to 1.6.
[0051] In a preferred embodiment of the present invention, when the base metal is copper, the peak intensity ratio of the 111 plane to the 220 plane (111 plane / 220 plane) in an X-ray diffraction (XRD) pattern is preferably 3.0 or less, more preferably 1.4 to 3.0.
[0052] When the electrical conductivity of annealed standard soft copper of the copper plating film of the present invention is taken as 100% IACS, the electrical conductivity is preferably 80% IACS or more, more preferably 85% IACS or more, even more preferably 90% IACS or more, particularly preferably 92% IACS or more, and most preferably 94% IACS or more. The electrical conductivity is determined by calculating the volume resistivity from the surface resistivity value by the four-point terminal method and the thickness of the plating film measured by a micrometer, and converting it into electrical conductivity as IACS%. The volume resistivity can be determined as the average value of multiple points (for example, five points at the top, bottom, left, right, and center) of the plating film sample. Note that IACS (international annealed copper standard)% is determined by using annealed standard soft copper (volume resistivity: 1.7241×10 -2 The electrical conductivity in μΩm is defined as 100% IACS.
[0053] In the base metal plating film of the present invention, the hydrophilic ND particle content is, for example, 0.5 to 25 area %, preferably 2 to 20 area %, and particularly preferably 5 to 15 area % of the area of the base metal plating film. The hydrophilic ND particle content (area %) can be measured by SEM observation of the cross section of the plating layer. In Comparative Example 2 and FIG. 4 of the present specification, the base metal plating film containing non-hydrophilic ND showed neither an increase in gloss nor an anti-oxidation effect, and therefore the present inventors have clarified that the "hydrophilicity" of ND particles is important for these effects.
[0054] The hydrophilic ND particles used in the present invention preferably have multiple or many hydrophilic functional groups, or more preferably are coated or modified with at least one hydrophilic polymer, so that aggregation can be prevented and a plating film having high gloss and excellent oxidation resistance can be obtained. Figure 1 is an enlarged schematic diagram showing an example of an ND particle having a surface modification group in the present invention. 1 indicates an ND particle having a surface modification group, 2 indicates an ND particle (part), and 3 indicates a surface modification group.
[0055] [Method of manufacturing base metal plating film] The base metal plating film of the present invention can be produced by utilizing a known electrolytic plating method (preferably an electrolytic composite plating method) or electroless plating method. More specifically, by immersing a member on which a plating film is to be formed (e.g., a conductive substrate such as a brass substrate) in a plating bath containing base metal ions and hydrophilic ND particles to perform electrolytic plating or electroless plating, the base metal ions are precipitated on the surface of the member together with the hydrophilic ND particles, and the hydrophilic ND particles can be incorporated into the base metal coating. By continuing this process until a desired thickness is reached, a base metal plating film (or a plating film composed of a base metal-hydrophilic ND particle composite material) having a structure in which hydrophilic ND particles are dispersed in a base metal matrix can be produced.
[0056] The thickness of the base metal plating film can be set appropriately depending on the application, and is, for example, about 0.1 to 1000 μm. When used to coat the surface of a conductive metal component as a connecting part such as a switch or connector, the thickness of the base metal plating film is, for example, about 0.1 to 50 μm.
[0057] (Base metal plating bath) The base metal plating bath in the present invention contains a plating solution and hydrophilic ND particles. The content of the hydrophilic ND particles in the base metal plating bath is, for example, in the range of 0.001 to 1.0 g / L (the lower limit is preferably 0.003 g / L, more preferably 0.006 g / L, even more preferably 0.01 g / L, and particularly preferably 0.03 g / L. The upper limit is preferably 0.8 g / L, more preferably 0.6 g / L, and particularly preferably 0.5 g / L), and is preferably 0.01 to 0.5 g / L. When the hydrophilic ND particle content is within the above range, the base metal plating film can have high gloss and oxidation resistance, and good adhesion to the substrate.
[0058] The base metal plating bath has excellent transparency because it contains hydrophilic ND particles in a highly dispersed (or colloidally dispersed) state, and the haze is preferably about 0 to 5, more preferably about 0 to 2, even more preferably about 0 to 1, particularly preferably about 0 to 0.5, and most preferably 0 to 0.4. The haze can be measured in accordance with JIS K7136.
[0059] The particle size (D10) of the hydrophilic ND particles in the base metal plating bath is, for example, 95 nm or less, preferably 60 nm or less, particularly preferably 50 nm or less, and most preferably 40 nm or less. The lower limit of the particle size (D10) of the hydrophilic ND particles is, for example, 10 nm.
[0060] The particle size (D50) of the hydrophilic ND particles in the base metal plating bath is, for example, 95 nm or less, preferably 70 nm or less, particularly preferably 60 nm or less, and most preferably 50 nm or less. The lower limit of the particle size (D50) of the hydrophilic ND particles is, for example, 20 nm.
[0061] The particle size (D90) of the hydrophilic ND particles in the base metal plating bath is, for example, 95 nm or less, preferably 90 nm or less, and particularly preferably 80 nm or less. The lower limit of the particle size (D90) of the hydrophilic ND particles is, for example, 50 nm. The particle size of the hydrophilic ND particles in the base metal plating bath can be measured by a dynamic light scattering method.
[0062] The base metal plating bath can be prepared, for example, by adding a hydrophilic ND particle dispersion to a plating solution described later. The electroless base metal plating bath may contain a water-soluble base metal salt, hydrophilic ND particles, a phosphorus source (in the case of electroless nickel-phosphorus alloy plating), a reducing agent, a complexing agent, etc. As the electroless base metal plating bath, an electroless nickel-phosphorus alloy base metal plating bath is preferable.
[0063] The concentration of the water-soluble base metal salt in the electrolytic and electroless base metal plating baths is, for example, 0.01 to 0.5 mol / L, and preferably 0.05 to 0.2 mol / L, calculated as the concentration of the base metal ion supplied to the base metal plating bath.
[0064] The reducing agent and phosphorus source contained in the electroless base metal plating bath may be, for example, a phosphinate such as sodium phosphinate. When a phosphinate is used, the concentration of the phosphinate in the base metal plating bath is, for example, 0.02 to 0.5 mol / L, and preferably 0.1 to 0.2 mol / L.
[0065] Examples of the complexing agent contained in the electrolytic and electroless base metal plating baths include citric acid, lactic acid, malic acid, glycolic acid, and salts thereof. Examples of citric acid include sodium citrate and potassium citrate. When citric acid and / or its salts are used, the concentration of citric acid and / or its salts in the electrolytic and electroless base metal plating baths is, for example, 0.02 to 1.0 mol / L, and preferably 0.1 to 0.5 mol / L.
[0066] The electrolytic and electroless base metal plating baths may contain other components in addition to those mentioned above, such as pH buffers and stabilizers for suppressing autolysis of the base metal plating bath.
[0067] The pH of the base metal plating bath is, for example, 5 to 11.
[0068] (Plating solution) The plating solution of the present invention contains components essential for preparing a plating film, but does not contain the above-mentioned hydrophilic ND particles. The plating solution contains at least base metal ions.
[0069] The plating solution can be prepared by mixing, for example, a water-soluble base metal salt, a conductivity salt, a complexing agent, an additive for adjusting the appearance and physical properties of the coating, etc. The water-soluble base metal salt exists as a base metal ion in the base metal plating bath. In addition, it may exist as an oxygen acid ion of the base metal or a base metal complex ion combined with a complexing agent.
[0070] Examples of plating solutions for base metal plating include base metal sulfate plating solutions containing base metal sulfate, sulfuric acid, chloride ions, etc.; base metal cyanide plating solutions containing base metal cyanide, sodium cyanide, alkali carbonate, Rochelle salt, etc.; and base metal pyrophosphate plating solutions containing base metal pyrophosphate, potassium pyrophosphate, ammonia water, potassium nitrate, etc.
[0071] (Hydrophilic ND particle dispersion and its preparation method) The hydrophilic ND particle dispersion liquid is obtained by dispersing hydrophilic ND particles in a dispersion medium (preferably water). The hydrophilic ND particle concentration in the hydrophilic ND particle dispersion liquid is, for example, about 1 to 100 g / L.
[0072] As the hydrophilic ND particles, from the viewpoint of excellent dispersibility, hydrophilic ND particles in which the hydrophilic functional groups of the ND particles are coated or modified with a hydrophilic polymer are preferred, and hydrophilic ND particles having a water-soluble polymer containing a polyglycerin chain are particularly preferred.
[0073] The particle size (D50) of the hydrophilic ND particles in the hydrophilic ND particle dispersion is, for example, 95 nm or less, preferably 70 nm or less, particularly preferably 60 nm or less, and most preferably 50 nm or less. The lower limit of the particle size (D50) of the hydrophilic ND particles is, for example, 10 nm. The particle size of the hydrophilic ND particles in the hydrophilic ND particle dispersion can be measured by dynamic light scattering (DLS).
[0074] The hydrophilic ND particle dispersion liquid can impart gloss to the resulting base metal plating film by adding it to a base metal plating bath, and can therefore be used, for example, as a brightener for base metal plating films.
[0075] (Preparation method of hydrophilic ND particle dispersion) An example of a method for producing a dispersion of hydrophilic ND particles modified with a polyglycerin chain is described below. Hydrophilic ND particles other than polyglycerin can be easily produced by those skilled in the art with reference to the general production method described above and the method for producing a dispersion of hydrophilic ND particles modified with a polyglycerin chain described below.
[0076] (generation process) First, an explosive with an electric detonator attached is placed inside a pressure-resistant container for detonation, and the container is sealed in a state where atmospheric gas and the explosive coexist. The container is made of iron, for example, and has a volume of 0.5 to 40 m. 3 As the explosive, a mixture of trinitrotoluene (TNT) and cyclotrimethylenetrinitramine, i.e., hexogen (RDX), can be used. The mass ratio of TNT to RDX (TNT / RDX) is, for example, in the range of 40 / 60 to 60 / 40.
[0077] In the production process, the electric detonator is then detonated to detonate the explosive inside the container. During detonation, the explosive used partially undergoes incomplete combustion, liberating carbon, which is used as raw material to generate ND particles due to the action of the pressure and energy of the shock wave generated by the explosion. The generated ND particles are very firmly assembled between adjacent primary particles or crystallites due to the action of van der Waals forces and the contribution of Coulomb interactions between crystal planes, forming an aggregate.
[0078] In the production step, the container and its interior are then allowed to cool by being left at room temperature for about 24 hours, and the temperature of the container and its interior is lowered. After this cooling, the ND particle crude product (including the aggregates of ND particles and soot produced as described above) adhering to the inner wall of the container is scraped off with a spatula, thereby obtaining the ND particle crude product.
[0079] (Acid treatment process) The acid treatment step is a step of removing metal oxides by applying a strong acid to the raw material ND particle crude product in, for example, an aqueous solvent. The ND particle crude product obtained by the detonation method is likely to contain metal oxides, and these metal oxides are oxides of Fe, Co, Ni, etc., derived from the container used in the detonation method. For example, by applying a specific strong acid in an aqueous solvent, the metal oxides can be dissolved and removed from the ND particle crude product. The strong acid used in the acid treatment is preferably a mineral acid, and examples of the strong acid include hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, and mixtures thereof. The concentration of the strong acid used in the acid treatment is, for example, 1 to 50 mass %. The acid treatment temperature is, for example, 70 to 150° C. The acid treatment time is, for example, 0.1 to 24 hours. The acid treatment can be performed under reduced pressure, normal pressure, or pressure. After such acid treatment, it is preferable to wash the solid content (including ND aggregates) with water, for example by decantation, until the pH of the precipitation liquid reaches, for example, 2 to 3. When the content of metal oxides in the ND particle crude product obtained by the detonation method is small, the acid treatment as described above may be omitted.
[0080] (Oxidation treatment process) The oxidation treatment process is a process in which graphite is removed from the ND particle crude product using an oxidizing agent. The ND particle crude product obtained by the detonation method contains graphite, which is derived from carbon that was liberated when the explosive used partially undergoes incomplete combustion and did not form ND crystals. For example, after the above-mentioned acid treatment, graphite can be removed from the ND particle crude product by applying a specific oxidizing agent in an aqueous solvent.
[0081] Examples of the oxidizing agent used in the oxidation treatment include chromic acid, chromic anhydride, dichromic acid, permanganic acid, perchloric acid, nitric acid, mixtures thereof, mixed acids of at least one acid selected from these with another acid (such as sulfuric acid), and salts thereof. In the present invention, it is preferable to use mixed acids (particularly mixed acids of sulfuric acid and nitric acid) because they are environmentally friendly and have excellent effects of oxidizing and removing graphite.
[0082] The mixing ratio of sulfuric acid and nitric acid in the mixed acid (the former / the latter; mass ratio) is preferably, for example, 60 / 40 to 95 / 5, because graphite can be efficiently oxidized and removed at a temperature of, for example, 130°C or higher (particularly preferably 150°C or higher; the upper limit is, for example, 200°C) even under pressure near normal pressure (for example, 0.5 to 2 atm). The lower limit is preferably 65 / 35, particularly preferably 70 / 30. The upper limit is preferably 90 / 10, particularly preferably 85 / 15, and most preferably 80 / 20.
[0083] If the ratio of nitric acid in the mixed acid exceeds the above range, the content of sulfuric acid having a high boiling point decreases, so that the reaction temperature becomes, for example, 120° C. or lower under pressure near normal pressure, and the graphite removal efficiency tends to decrease. On the other hand, if the ratio of nitric acid in the mixed acid falls below the above range, the content of nitric acid that greatly contributes to the oxidation of graphite decreases, so that the graphite removal efficiency tends to decrease.
[0084] The amount of the oxidizing agent (particularly, the mixed acid) used is, for example, 10 to 50 parts by mass, preferably 15 to 40 parts by mass, and particularly preferably 20 to 40 parts by mass, relative to 1 part by mass of the ND particle crude product. The amount of sulfuric acid used in the mixed acid is, for example, 5 to 48 parts by mass, preferably 10 to 35 parts by mass, and particularly preferably 15 to 30 parts by mass, relative to 1 part by mass of the ND particle crude product, and the amount of nitric acid used in the mixed acid is, for example, 2 to 20 parts by mass, preferably 4 to 10 parts by mass, and particularly preferably 5 to 8 parts by mass, relative to 1 part by mass of the ND particle crude product.
[0085] When the mixed acid is used as the oxidizing agent, a catalyst may be used together with the mixed acid. By using a catalyst, the efficiency of removing graphite can be further improved. An example of the catalyst is copper (II) carbonate. The amount of the catalyst used is, for example, about 0.01 to 10 parts by mass with respect to 100 parts by mass of the ND particle crude product.
[0086] The oxidation treatment temperature is, for example, 100 to 200° C. The oxidation treatment time is, for example, 1 to 24 hours. The oxidation treatment can be carried out under reduced pressure, normal pressure, or increased pressure.
[0087] (drying process) In this method, it is preferable to provide a drying step next, for example, by evaporating the liquid from the hydrophilic ND particle-containing solution having hydrophilic functional groups obtained through the above steps using a spray drying device, evaporator, or the like, and then drying the resulting residual solid by heat drying in a drying oven. The heat drying temperature is, for example, 40 to 150°C. By passing through such a drying step, ND powder is obtained.
[0088] (Oxygen oxidation process) In the oxygen oxidation step, a gas atmosphere furnace is used to heat the ND powder in a gas atmosphere of a predetermined composition containing oxygen. Specifically, the ND powder is placed in a gas atmosphere furnace, an oxygen-containing gas is supplied to or passed through the furnace, and the temperature inside the furnace is raised to a temperature condition set as the heating temperature, whereby the oxygen oxidation treatment is performed.
[0089] The temperature condition of the oxygen oxidation treatment is, for example, 250 to 500°C. In order to obtain hydrophilic ND particles having a negative zeta potential, the temperature condition of this oxygen oxidation treatment is preferably a relatively high temperature, for example, 400 to 450°C. The oxygen-containing gas is a mixed gas containing an inert gas in addition to oxygen. Examples of the inert gas include nitrogen, argon, carbon dioxide, and helium. The oxygen concentration of the mixed gas is, for example, 1 to 35% by volume.
[0090] (Hydrogenation process) Moreover, when hydrophilic ND particles having a positive zeta potential are desired, a hydrogenation process is performed after the above-mentioned oxygen oxidation process. In the hydrogenation process, the ND powder that has been subjected to the oxygen oxidation process is heated in a gas atmosphere of a predetermined composition containing hydrogen using a gas atmosphere furnace. Specifically, a hydrogen-containing gas is supplied or passed through a gas atmosphere furnace in which the ND powder is disposed, and the temperature inside the furnace is raised to a temperature condition set as the heating temperature, and hydrogenation is performed. The temperature condition of this hydrogenation process is, for example, 400 to 800°C. Moreover, the hydrogen-containing gas used in this embodiment is a mixed gas containing an inert gas in addition to hydrogen. Examples of the inert gas include nitrogen, argon, carbon dioxide, and helium. The hydrogen concentration of the mixed gas is, for example, 1 to 50% by volume.
[0091] (Crushing process) Even after being refined through a series of processes as described above, the hydrophilic ND particles often take the form of aggregates (secondary particles) in which primary particles are aggregated through very strong interactions between them. Therefore, it is preferable to perform a crushing process to separate the primary particles from the aggregates. Specifically, first, the ND powder that has been subjected to the oxygen oxidation process or the subsequent hydrogenation process is suspended in pure water to prepare a slurry containing ND particles having hydrophilic functional groups (OH, COOH, NH2, etc.). In preparing the slurry, a centrifugation process may be performed to remove relatively large aggregates from the hydrophilic ND particle suspension, or an ultrasonic treatment may be performed on the ND particle suspension having hydrophilic functional groups. Then, the slurry is subjected to a wet crushing process. The crushing process can be performed using, for example, a high shear mixer, a high shear mixer, a homomixer, a ball mill, a bead mill, a high-pressure homogenizer, an ultrasonic homogenizer, or a colloid mill. The crushing process may be performed by combining these. From the viewpoint of efficiency, it is preferable to use a bead mill.
[0092] By passing through such a disintegration step, an ND particle aqueous dispersion containing ND primary particles having hydrophilic functional groups can be obtained. The dispersion obtained through the disintegration step may be subjected to a classification operation in order to remove coarse particles. For example, a classification device can be used to remove coarse particles from the dispersion by a classification operation utilizing centrifugation.
[0093] (drying process) In this method, it is preferable to subsequently provide a drying step, for example, by evaporating the liquid from the aqueous dispersion of ND particles having hydrophilic functional groups obtained through the above steps using a spray drying device, evaporator, or the like, and then drying the resulting residual solid by heating and drying in a drying oven. The heating and drying temperature is, for example, 40 to 150° C. Through such a drying step, ND particles having hydrophilic functional groups are obtained as a powder.
[0094] (modification process) Hydrophilic ND particles modified with polyglycerin chains can be obtained, for example, by directly ring-opening polymerizing glycidol on ND particles having hydrophilic functional groups obtained through the above process. ND particles have carboxyl groups and hydroxyl groups on their surfaces that are generated during the manufacturing process, and by reacting these functional groups with glycidol, the surface of the ND can be modified with a hydrophilic polymer.
[0095] The reaction (ring-opening polymerization) between ND particles having a hydrophilic functional group and glycidol can be carried out, for example, by adding glycidol and a catalyst to ND particles having a hydrophilic functional group under an inert gas atmosphere, and heating to 50 to 100° C. The catalyst can be an acidic catalyst or a basic catalyst. Examples of the acidic catalyst include trifluoroboron etherate, acetic acid, and phosphoric acid, and examples of the basic catalyst include triethylamine, pyridine, dimethylaminopyridine, and triphenylphosphine.
[0096] The amount of glycidol used in the ring-opening polymerization is, for example, 20 parts by mass or more, and preferably 20 to 150 parts by mass, relative to 1 part by mass of ND particles having a hydrophilic functional group. If the amount of glycidol used is below the above range, sufficient dispersibility tends to be difficult to obtain.
[0097] After the reaction is completed, the reaction product obtained is preferably purified, for example, by filtration, centrifugation, extraction, washing with water, neutralization, or a combination of these. This results in a hydrophilic ND particle dispersion in the present invention (preferably, a hydrophilic ND particle aqueous dispersion). Glycidol is used to produce ND particles modified with polyglycerin, but ND particles modified with a hydrophilic polymer other than polyglycerin, or ND particles modified with a hydrophilic polymer, can be easily produced by a person skilled in the art by referring to the above description and known techniques.
[0098] [Electronic components] The electronic component of the present invention is characterized by having the above-mentioned base metal plating film. The electronic component of the present invention may have other plating films in addition to the above-mentioned base metal plating film, for example, may have one or more undercoat plating films. The electronic component of the present invention includes, for example, connection parts (e.g., connectors) for electronic devices such as personal digital assistants (PDAs) and mobile phones.
[0099] [Brightener] The brightener for base metal plating films of the present invention is characterized by containing the above-mentioned hydrophilic ND particles.
[0100] The gloss agent may contain other components in addition to the hydrophilic ND particles, but the proportion of the content of the hydrophilic ND particles in the total amount of the gloss agent is, for example, 50 mass% or more, preferably 60 mass% or more, particularly preferably 70 mass% or more, most preferably 80 mass% or more, and particularly preferably 90 mass% or more.
[0101] [Antioxidants] The antioxidant for base metal plating films of the present invention is characterized by containing the above-mentioned hydrophilic ND particles.
[0102] The antioxidant may contain other components in addition to the hydrophilic ND particles, but the proportion of the content of the hydrophilic ND particles in the total amount of the antioxidant is, for example, 50 mass% or more, preferably 60 mass% or more, particularly preferably 70 mass% or more, most preferably 80 mass% or more, and particularly preferably 90 mass% or more. EXAMPLES
[0103] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The ND particle concentration, particle size, and zeta potential were measured by the following methods.
[0104] <ND particle concentration> The ND particle concentration of the ND particle aqueous dispersion was calculated based on the weighed value of 3 to 5 g of the dispersion and the value of the dried matter (powder) remaining after evaporating the water from the weighed dispersion by heating, which was weighed using a precision balance.
[0105] <Particle size> The particle sizes (median diameter, D10, D50, and D90) of the ND particles contained in the ND particle aqueous dispersion and the base metal plating bath were measured by the dynamic light scattering method (non-contact backscattering method) using an apparatus manufactured by Malvern (product name "Zetasizer Nano ZS").
[0106] Zeta potential The zeta potential of the ND particles contained in the ND particle aqueous dispersion was measured by laser Doppler electrophoresis using a Malvern device (product name "Zetasizer Nano ZS"). The ND particle aqueous dispersion used for the measurement was diluted with ultrapure water so that the ND particle concentration was 0.2 mass % and then irradiated with ultrasonic waves using an ultrasonic cleaner. The zeta potential was measured at a temperature of 25°C.
[0107] Preparation Example 1 An aqueous dispersion of hydrophilic ND particles was prepared through the following steps.
[0108] (generation process) First, the formed explosives with electric detonators attached were placed in a pressure-resistant container (made of iron, volume: 15 m 3 ) and the container was sealed. 0.50 kg of a mixture of TNT and RDX (TNT / RDX (mass ratio) = 50 / 50) was used as the explosive. Next, an electric detonator was detonated to detonate the explosive in the container. Next, the container and its inside were allowed to cool for 24 hours at room temperature. After this cooling, the ND particle crude product (including the aggregated body of ND particles and soot generated by the above detonation method) adhering to the inner wall of the container was collected to obtain the ND particle crude product.
[0109] (Acid treatment process) Next, the ND particle crude product obtained in the above step was subjected to an acid treatment. Specifically, 6 L of 10 mass % hydrochloric acid was added to 200 g of the ND particle crude product to obtain a slurry, which was then subjected to a heat treatment (heating temperature: 85 to 100°C) for 1 hour under reflux under normal pressure conditions. Next, after cooling, the solid content (including ND aggregates and soot) was washed with water by decantation. The solid content was repeatedly washed with water by decantation until the pH of the precipitation liquid reached 2 from the low pH side.
[0110] (Oxidation treatment process) Next, a mixed acid treatment was performed. Specifically, 6 L of a 98 mass% aqueous sulfuric acid solution and 1 L of a 69 mass% aqueous nitric acid solution were added to the precipitate liquid (including ND aggregates) obtained by decantation after the acid treatment to form a slurry, and then this slurry was subjected to a heat treatment (heating temperature: 140 to 160°C) for 48 hours under normal pressure conditions and reflux. Next, after cooling, the solid matter (including ND aggregates) was washed with water by decantation. The supernatant liquid at the beginning of the washing was colored, but the solid matter was repeatedly washed with water by decantation until the supernatant liquid became visually transparent.
[0111] (drying process) Next, 1000 mL of the liquid containing ND particles having hydrophilic functional groups obtained through the above-mentioned water washing treatment was spray-dried using a spray drying device (product name "Spray Dryer B-290", manufactured by Nippon Buchi Co., Ltd.) to obtain 50 g of ND powder.
[0112] (Oxygen oxidation process) Next, 4.5 g of the ND powder obtained as described above was placed still in the core tube of a gas atmosphere furnace (trade name "Gas Atmosphere Tube Furnace KTF045N1", manufactured by Koyo Thermo System Co., Ltd.). Nitrogen gas was continuously passed through the core tube at a flow rate of 1 L / min for 30 minutes, and then the flowing gas was switched from nitrogen to a mixed gas of oxygen and nitrogen, and the mixed gas was continuously passed through the core tube at a flow rate of 1 L / min. The oxygen concentration in the mixed gas was 4% by volume. After switching to the mixed gas, the temperature inside the furnace was raised to 400 °C, which was the set heating temperature. Regarding the heating rate, it was 10 °C / min up to 380 °C, which was 20 °C lower than the set heating temperature, and then 1 °C / min from 380 °C to 400 °C. Then, while maintaining the temperature condition inside the furnace at 400 °C, an oxygen oxidation treatment was performed on the ND powder inside the furnace. The treatment time was 3 hours.
[0113] After the oxygen oxidation treatment, the evaluation of oxygen-containing functional groups such as carboxyl groups in the ND particles was carried out by the following FT-IR analysis. From the spectrum obtained in this analysis, the absorption near 1780 cm -1 attributed to the stretching vibration of C=O was detected as the main peak. From this, it was confirmed that the ND powder mainly contained ND particles (ND-COOH) having a plurality of carboxyl groups as surface functional groups.
[0114] <FT-IR Analysis Conditions> Fourier transform infrared spectroscopy (FT-IR) was performed using an FT-IR device (trade name "Spectrum400 type FT-IR", manufactured by PerkinElmer Japan Co., Ltd.). In this measurement, the infrared absorption spectrum was measured while heating the sample to 150 °C under a vacuum atmosphere. For heating under a vacuum atmosphere, a Model-HC900 type Heat Chamber and a TC-100WA type Thermo Controller manufactured by S.T. Japan Co., Ltd. were used in combination.
[0115] (Crushing Process) First, 0.3 g of the ND powder that had been subjected to the oxygen oxidation process and 29.7 mL of pure water were mixed in a 50 mL sample bottle to obtain about 30 mL of slurry. Next, the pH of the slurry was adjusted by adding 1N aqueous sodium hydroxide solution, and then ultrasonic irradiation was performed for 2 hours using an ultrasonic irradiator (product name "ultrasonic cleaner AS-3", manufactured by AS ONE Co., Ltd.). After this, bead milling was performed using a bead milling device (product name "parallel four-cylinder sand grinder LSG-4U-2L type", manufactured by IMEX Co., Ltd.). Specifically, 30 mL of the slurry after ultrasonic irradiation and zirconia beads with a diameter of 30 μm were sealed in a 100 mL mill container, a vessel (manufactured by IMEX Co., Ltd.), and the device was driven to perform bead milling. In this bead milling, the amount of zirconia beads charged was about 33% of the volume of the mill container, the rotation speed of the mill container was 2570 rpm, and the milling time was 2 hours.
[0116] Next, the slurry that had been subjected to the disintegration step was subjected to a centrifugal separation process using a centrifugal separator (classification operation). The centrifugal force in this centrifugation process was 20,000×g, and the centrifugation time was 10 minutes.
[0117] Next, 25 mL of the supernatant of the ND particle-containing solution that had been subjected to the centrifugal separation process was collected to obtain an ND particle aqueous dispersion (ND-COOH). The ND particle concentration in the ND particle aqueous dispersion was 11.8 g / L. The pH was measured using pH test paper (product name "Three Band pH Test Paper", manufactured by AS ONE Corporation) and found to be 9.33. The particle size D50 was 3.97 nm, the particle size D90 was 7.20 nm, and the zeta potential was -42 mV.
[0118] (modification process) The ND particle aqueous dispersion obtained above was dried using an evaporator to obtain a black dry powder. The obtained dry powder (100 mg) was added to 12 mL of glycidol in a glass reactor, and dissolved by ultrasonic treatment at room temperature for 2 hours using an ultrasonic cleaner (product name "BRANSON2510", manufactured by Marshall Scientific). This was reacted at 140°C for 20 hours while stirring under a nitrogen atmosphere. After cooling the reaction mixture, 120 mL of methanol was added, ultrasonic treatment was performed, and then centrifugation was performed at 50400G for 2 hours to obtain a precipitate. 120 mL of methanol was added to this precipitate, and the washing-centrifugation process was repeated five times in the same manner. Finally, the precipitate was dialyzed against pure water using a dialysis membrane (Spectra / Pro dialysis membrane, MWCO: 12-14 kDa), the residual methanol was replaced with water, and the mixture was freeze-dried to obtain a gray powder of hydrophilic ND particles modified with polyglycerin (PG-ND particles).
[0119] The ratio of ND particles to surface modifying groups was measured by TG-DTA thermal analysis, and was found to be ND particles:surface modifying groups=1:0.7.
[0120] The PG-ND gray powder and water were added, and the concentration was adjusted to 10 g / L based on the mass of the ND particles to obtain a PG-ND particle aqueous dispersion.
[0121] Example 1 The PG-ND particle aqueous dispersion obtained in Preparation Example 1 was added to a copper plating solution (product name "Electrolytic Plating Solution", manufactured by Kiyokawa Plating Industry Co., Ltd.) to obtain a plating bath (1) (PG-ND particle concentration in the plating bath: 1 g / L, CuSO4·5H2O concentration: 5 mass %).
[0122] When the particle sizes of the PG-ND particles in the plating bath (1) were measured, the particle size (D10) was 30 nm, the particle size (D50) was 44 nm, and the particle size (D90) was 76 nm.
[0123] The plating bath (1) was transparent and had no turbidity whatsoever.
[0124] A brass plate (length 20 mm × width 20 mm × thickness 1 mm) [manufactured by Kiyokawa Plating Co., Ltd.] as the target component for plating film formation was degreased and cleaned.
[0125] The brass plate was plated in a plating bath (1) at pH 0.1, a liquid temperature of 28°C, and a current density of 2 A / dm 2 The mixture was plated for 20 minutes under stirring under the above conditions to form a plating film (copper plating film) made of a copper-ND particle composite material on the brass plate (cathode: brass plate, anode: copper plate). The obtained brass plate with the copper plating film had ND particles highly dispersed uniformly and had a smooth surface.
[0126] Example 2 A plating bath (2) (PG-ND particle concentration in the plating bath: 0.5 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed, and a brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (2) was used.
[0127] Example 3 A plating bath (3) (PG-ND particle concentration in the plating bath: 0.2 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed, and a brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (3) was used.
[0128] Example 4 A plating bath (4) (PG-ND particle concentration in the plating bath: 0.1 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed. A brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (4) was used.
[0129] Example 5 A plating bath (5) (PG-ND particle concentration in the plating bath: 0.05 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed. A brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (5) was used.
[0130] Example 6 A plating bath (6) (PG-ND particle concentration in the plating bath: 0.01 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed. A brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (6) was used.
[0131] Example 7 A plating bath (7) (PG-ND particle concentration in the plating bath: 0.001 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed. A brass plate having a copper plating film was obtained in the same manner as in Example 1, except that the obtained plating bath (7) was used.
[0132] Comparative Example 1 A brass plate having a copper plating film was obtained in the same manner as in Example 1, except that a copper plating solution (product name "Electrolytic Plating Solution", manufactured by Kiyokawa Plating Industry Co., Ltd.) plating bath (6) (not including an ND particle dispersion) was used instead of plating bath (1). The plating film formed on the brass plate had an uneven surface and lacked smoothness.
[0133] <Glossiness measurement> The glossiness of the plating films obtained in Examples 1 to 7 and Comparative Example 1 was measured using a gloss meter "High Gloss Gloss Checker IG-410" (manufactured by Horiba, Ltd.) under the following conditions: glossiness m0 (specular reflectance 100%).
[0134] Light source: LED (wavelength: 890nm) Angle of incidence: 60° (for 100% reflection, the gloss is 1000 (no units)) The results are summarized in Table 1 below.
[0135] From Table 1 below, it can be seen that the addition of ND particles increases the gloss of the copper plating film surface, such as copper.
[0136] [Table 1]
[0137] 2 (Comparative Example 1) and 3 (Example 4) show the X-ray diffraction results immediately after production and 7 days after for the plating films formed on the brass plates in Example 4 and Comparative Example 1. The copper plating film in Comparative Example 1 showed a copper oxide (CuO) peak after 1 week and was colored reddish brown, but the copper plating film in Example 4 did not show a copper oxide (CuO) peak even after 1 week, and no difference was observed with the naked eye between immediately after production and 7 days after.
[0138] These results demonstrate that hydrophilic ND particles can suppress the oxidation of base metal plating films.
[0139] Comparative Example 2 Non-hydrophilic PG-unmodified ND was added to a copper plating bath (Kiyokawa Plating Co., Ltd.) at 200 ppm. The concentration of ND (manufactured by Daicel Co., Ltd., before PG modification) was the same as that in the case of the presence of PG. Plating was performed under the same conditions as in Example 1 using PG-modified ND while stirring. The same samples were used to confirm the gloss and oxidation prevention effect. The results of measuring the gloss immediately after production of the obtained plating film (Comparative Example 2, Examples 3 and 4) are shown in Table 2. As a result of copper plating with PG-unmodified ND, the gloss was about the same as that in the case without ND, and a clear difference was observed from the gloss when PG-modified ND was added. Furthermore, XRD measurement of the copper plating film of Comparative Example 2 was performed immediately after plating and 5 days later. The results are shown in FIG. 4. Copper oxide was confirmed 5 days after the production of the plating film, and the oxidation prevention effect confirmed with PG-ND particles was not observed.
[0140] [Table 2]
[0141] [Test Example 1] Copper plating baths were prepared in the same manner as in Example 1, except that the concentrations of PG-ND particles in the copper plating bath were 0 ppm, 200 ppm (0.02%), 400 ppm (0.04%), 600 ppm (0.06%), and 1000 ppm (0.1%), and the haze was measured. The results are shown in Table 3.
[0142] [Table 3]
[0143] [Test Example 2] In Preparation Example 1, the crystal structure of the PG-unmodified ND particles obtained by the detonation method was analyzed using an X-ray diffraction apparatus (product name "Smart Lab", manufactured by Rigaku Corporation). As a result, a strong diffraction peak was observed at the diffraction peak position of diamond, i.e., the diffraction peak position from the (111) plane of the diamond crystal, and it was confirmed that the PG-unmodified ND particles were diamond.
[0144] Next, small angle X-ray scattering measurements (SAXS method) were performed using an X-ray diffraction device (trade name "Smart Lab", manufactured by Rigaku Corporation) for the PG-unmodified ND particles and PG-ND particles obtained in Preparation Example 1, and the ND particles (PG-unmodified and PG-modified) obtained by the shock compression method, and the primary particle diameter of nanodiamonds was estimated in the scattering angle range of 1° to 3° using particle size distribution analysis software (trade name "NANO-Solver", manufactured by Rigaku Corporation). In this estimation, the primary nanodiamond particles were assumed to be spherical and had a particle density of 3.51 g / cm. 3 It was assumed that the ND particles obtained by the shock compression method were SCM Nanodiamond (trade name, manufactured by Sumiishi Materials Co., Ltd.), and the PG-modified ND particles obtained by the shock compression method were obtained by modifying the above ND particles with PG in the same manner as in Preparation Example 1. The results of particle size measurement by the SAXS method are shown in Table 4.
[0145] [Table 4]
[0146] [Test Example 3] The plating films obtained in Example 1 (copper plating solution containing 200 ppm of PG-ND), Comparative Example 1 (plating solution containing no ND), and Comparative Example 2 (plating solution containing PG-unmodified ND) were measured for the diffraction peaks of the 111 plane of copper oxide immediately after plating, 5 days after plating, and 7 days after plating by grazing incidence X-ray diffraction as described below.
[0147] (1) Small angle incidence X-ray diffraction method Grazing incidence X-ray diffraction (GIXD) was used to analyze the surface structure of the copper-plated surface. This method utilizes the phenomenon that total reflection occurs when X-rays are incident on a flat surface of a material, and measures reflection, refraction, and diffraction while slightly changing the angle around the angle at which total reflection occurs. This time, measurements were taken using SmartLab (manufactured by Rigaku Corporation) with an incident angle of approximately 0.7° and a measurement angle of 30° to 100°.
[0148] (2) Storage conditions of plating film The brass plates having the copper plating film obtained in Example 1 and Comparative Examples 1 and 2 were stored indoors out of direct sunlight for 5 days or 1 week (room temperature of about 25° C., humidity of about 50%).
[0149] (3) Measurement results The results are shown in Table 5.
[0150] [Table 5]
[0151] After 7 days, the peak intensity of the copper oxide 111 plane relative to the peak intensity of the copper 111 plane was 2.5% in the case without ND (Comparative Example 1), whereas the copper oxide peak was 0.1% in the case of the PG-modified ND (Example 3).
[0152] [Example 8 and Comparative Example 3] Using the following tin (Sn) plating solution, Sn plating of a brass plate was carried out in the same manner as in Example 1 (PG-ND particle concentration in the Sn plating bath: 0.2 g / L (Example 8) or 0 g / L (Comparative Example 3)), to obtain a brass plate having a Sn plating film. The gloss and surface roughness (Ra) of the obtained brass plate having a Sn plating film were measured, and the results are shown in Table 6. ·Sn plating Liquid composition: stannous sulfate 30g / L, sulfuric acid 130g / L Plating temperature: 10℃ Current density: 2A / dm 2 Plating time: 10 minutes
[0153] [Example 9 and Comparative Example 4] Using the following nickel (Ni) plating solution and plating conditions, Ni plating of a brass plate was performed in the same manner as in Example 1 (PG-ND particle concentration in the Ni plating bath: 0.2 g / L (Example 9) or 0 g / L (Comparative Example 4)), to obtain a brass plate having a Ni plating film. The gloss and surface roughness (Ra) of the obtained brass plate having a Ni plating film were measured, and the results are shown in Table 6. Nickel plating Liquid composition: Nickel sulfate 250g / L, nickel chloride 40g / L, boric acid 30g / L Plating temperature: 50℃ Current density: 2A / dm 2 Plating time: 25 minutes
[0154] [Example 10 and Comparative Example 5] The following zinc (Zn) plating solution and plating conditions were used to perform Zn plating on a brass plate in the same manner as in Example 1 (PG-ND particle concentration in the Zn plating bath: 0.2 g / L (Example 10) or 0 g / L (Comparative Example 5)), to obtain a brass plate having a Zn plating film. The gloss and surface roughness (Ra) of the obtained brass plate having a Zn plating film were measured, and the results are shown in Table 6. Zinc plating Liquid composition: zinc oxide 10g / L, sodium hydroxide 100g / L Plating temperature: Room temperature Current density: 2A / dm 2 Plating time: 18 minutes
[0155] [Example 11 and Comparative Example 6] Using the following permalloy (Ni and Fe alloy) plating solution and plating conditions, permalloy plating of a brass plate was carried out in the same manner as in Example 1 and Comparative Example 1 (PG-ND particle concentration in the permalloy plating bath: 0.2 g / L (Example 11) or 0 g / L (Comparative Example 6)), to obtain a brass plate having a permalloy plating film. The gloss and surface roughness (Ra) of the obtained brass plate having a permalloy plating film were measured, and the results are shown in Table 6. ·Permalloy plating Liquid composition: Nickel sulfate 250g / L, nickel chloride 40g / L, boric acid 30g / L, ferrous sulfate 24g / L, malonic acid 5g / L, Plating temperature: 50℃ Current density: 2A / dm 2 Plating time: 25 minutes
[0156] <Surface roughness (Ra) measurement> The surface roughness (Ra) of the plating films obtained in Examples 8 to 11 and Comparative Examples 3 to 6 was measured using a high-precision shape measuring system KS-1100 (manufactured by KEYENCE Corporation).
[0157] [Table 6]
[0158] It was revealed that the glossiness, surface smoothness, and indentation hardness (surface hardness) of the plating film can be improved by adding PG-ND particles to various plating solutions. It is believed that low surface roughness (Ra) is related to the improvement of glossiness.
[0159] [Test Example 4] For the plating films obtained in Examples 3, 9, and 11, and Comparative Examples 1, 4, and 6, the indentation hardness (surface hardness) was measured under the following conditions using a microindentation hardness tester (product name "ENT-2100", manufactured by Elionix Co., Ltd.). Indenter: Berkovich indenter Loading conditions: (i) Start load_0mN → Load_20mN, 10s (ii) Starting load_20mN → Load_20mN, 10s (iii) Starting load 20mN → End load 0mN, 10s Microhardness tester The results are shown in Table 7.
[0160] [Table 7]
[0161] Example 12 A plating bath (12) (PG-ND particle concentration in the plating bath: 0.02 g / L) was obtained in the same manner as in Example 1, except that the amount of the PG-ND particle aqueous dispersion obtained in Preparation Example 1 was changed. Using the obtained plating bath (12), a stainless steel plate having a copper plating film was obtained in the same manner as in Example 1, except that the brass plate was changed to a stainless steel plate.
[0162] Comparative Example 7 A stainless steel plate having a copper plating film was obtained in the same manner as in Comparative Example 1, except that the plating bath (6) of Comparative Example 1 was used and a stainless steel plate was used instead of the brass plate.
[0163] [Test Example 5] The copper plating films were peeled off from the stainless steel plates obtained in Example 12 (using a copper plating solution containing 20 ppm of PG-ND) and Comparative Example 7 (using a plating solution containing no ND), and the plating films were placed on a glass plate to measure the thickness of the plating film with a micrometer, and the electrical conductivity was measured under the following conditions. Conductivity measuring device: Loresta GX, manufactured by Mitsubishi Chemical Analytech Sample size: 1cm 2 Measurement points: top, bottom, left, right, center (5 points) Measurement method: The plating film was peeled off from the stainless steel plate and measured on a separately prepared glass plate.
[0164] Specifically, the thickness of the plating film measured with a micrometer was input into the Loresta GX, and the volume resistivity was measured (four-point terminal method). The volume resistivity was measured using annealed standard soft copper (volume resistivity: 1.7241×10 -2 The conductivity was converted to electrical conductivity with the electrical conductivity in μΩm set as 100% IACS. The results are shown in Table 8.
[0165] [Table 8]
[0166] It was revealed that the conductivity of copper plating produced from a plating bath containing the hydrophilic nanodiamond of the present invention (PG-ND) was improved compared to copper plating without the addition. The base metal plating film of the present invention to which hydrophilic nanodiamond (PG-ND) has been added has the unexpected effect of preventing an increase in crystallite size, maintaining hardness, and improving electrical conductivity.
[0167] [Test Example 6] The crystallite sizes of the 111 and 220 planes were measured for the copper plating films obtained in Example 3 (copper plating solution containing 200 ppm of PG-ND) and Comparative Example 1 (copper plating solution not containing ND). The crystallite sizes were measured by X-ray diffraction (XRD) using CuKα rays as the X-ray source, and were calculated using Scherrer's formula from the half-width and diffraction angle of the diffraction peak. The measuring device was a Rigaku [SmartLab], and the optical system used was the focusing method. The results are shown in Table 9. The XRD pattern of the copper plating film is shown in Figure 5, and the peak intensity ratios of the 111 and 220 planes are shown in Table 10.
[0168] [Table 9]
[0169] [Table 10]
[0170] It was revealed that the copper plating film containing PG-ND obtained in Example 3 had small crystallite sizes in both the 111 and 220 faces and was excellent in indentation hardness (surface hardness).
[0171] [Test Example 7] For the plating films obtained in Example 9 (nickel plating solution containing 200 ppm of PG-ND) and Comparative Example 4 (nickel plating solution not containing ND), the crystallite sizes of the 111 and 200 faces of the nickel plating were measured 3 months after plating. The crystallite size was measured by X-ray diffraction (XRD) using CuKα rays as the X-ray source, and was calculated using Scherrer's formula from the half-width and diffraction angle of the diffraction peak. The measuring device used was a Rigaku [SmartLab], and the optical system used was the focusing method. The results are shown in Table 11.
[0172] [Table 11]
[0173] It was revealed that the nickel plating film containing PG-ND obtained in Example 9 had small crystallite sizes in both the 111 and 200 faces and was excellent in indentation hardness (surface hardness).
[0174] [Test Example 8] For the plating films obtained in Example 9 (nickel plating solution containing 200 ppm of PG-ND) and Comparative Example 4 (nickel plating solution containing no ND), cross sections were prepared using a focused ion beam processing device and observed using backscattered electron images. Device name: FIB-SEM device (FEI Versa3D DualBeam). Figure 6(a) shows the plating film not containing ND particles of Comparative Example 1, and it can be seen that the surface roughness (Ra) is large. Figure 6(b) shows the plating film containing ND particles of Example 1, and the small black dots indicated by the arrows are ND particles.
[0175] [Test Example 9] For the plating film obtained in Example 1 (copper plating solution containing 200 ppm of PG-ND), the carbon content (C1s) in the Cu plating film was measured by X-ray photoelectron spectroscopy (XPS) using an ULVAC-PHI Corporation (PHI5800 ESCA system). The results are shown in Figure 7. Carbon was detected in the Cu film. [Explanation of symbols]
[0176] 1. ND particles with surface modification groups 2 ND particles (partial) 3 Surface modification group
Claims
1. A base metal matrix and hydrophilic nanodiamond particles dispersed in the base metal matrix; The amount of hydrophilic polymer introduced into the hydrophilic nanodiamond particles is 0.4 to 1.0 parts by mass per part by mass of the nanodiamond particle portion. Base metal plating film.
2. The base metal plating film described in claim 1 has a glossiness at an incident angle of 60° that is 10 or more higher than that of the same base metal plating film as described above except that it does not contain the hydrophilic nanodiamond particles.
3. The base metal plating film according to claim 1 or 2, wherein the increase in base metal oxide after storage for 7 days at 25°C and 50% humidity in a room away from direct sunlight immediately after production is less than 1% in terms of the intensity ratio of the diffraction peak of the base metal oxide to the diffraction peak of the base metal measured by grazing incidence X-ray diffraction.
4. The base metal plating film according to any one of claims 1 to 3, which is free of a surfactant.
5. The base metal plating film according to any one of claims 1 to 4, wherein the hydrophilic nanodiamond particles are nanodiamond particles of the following (i) or (ii): (i) Nanodiamond particles coated with a hydrophilic polymer; (ii) Nanodiamond particles modified with hydrophilic polymers.
6. The plating film according to any one of claims 1 to 5, wherein the base metal is at least one selected from the group consisting of iron, nickel, zinc, copper, tin, aluminum, tungsten, molybdenum, tantalum, magnesium, cobalt, bismuth, cadmium, titanium, zirconium, antimony, manganese, beryllium, chromium, germanium, vanadium, gallium, hafnium, indium, niobium, permalloy, rhenium, and thallium.
7. The base metal plating film according to any one of claims 1 to 6, wherein the average particle diameter (D50) of the hydrophilic nanodiamond particles dispersed in the base metal matrix is in the range of 4 to 95 nm as measured by SEM method.
8. 6. The base metal plating film according to claim 5, wherein the hydrophilic polymer is selected from the group consisting of polyglycerin, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, poly(meth)acrylic acid, polyacrylamide, polyethyleneimine, vinyl ether polymers, cellulose derivatives, water-soluble polyesters, water-soluble phenolic resins, and natural polymeric polysaccharides.
9. The base metal plating film according to any one of claims 1 to 8, wherein the base metal is copper, the crystallite size (A) of the 111 plane is 100 nm or less, the crystallite size (B) of the 220 plane is 80 nm or less, and the crystallite size ratio (A / B) of the 111 plane to the 220 plane is 1.3 or more.
10. 9. The base metal plating film according to claim 1, wherein the base metal is copper, and the peak intensity ratio (111 plane / 220 plane) of the 111 plane to the 220 plane in the X-ray diffraction pattern is 3.0 or less.
11. The base metal plating film according to any one of claims 1 to 8, wherein the base metal is nickel, the crystallite size (A) of the 111 plane is 25 nm or less, the crystallite size (C) of the 200 plane is 23 nm or less, and the crystallite size ratio (A / C) of the 111 plane to the 200 plane is 1.1 or more.
12. A method for producing a plating film described in any one of claims 1 to 11, characterized in that a specimen is immersed in a base metal plating bath containing base metal ions and hydrophilic nanodiamond particles, the concentration of the nanodiamond particles being 0.001 to 1 g / L, and electrolytic plating is performed.
13. The method for producing a plating film according to claim 12, wherein the haze of the base metal plating bath is 0 to 0.
5.
14. An electronic component comprising the plating film according to any one of claims 1 to 11.
Citation Information
Patent Citations
Surface-modified nanodiamond and producing method thereof
JP2010248023A
Composite plating solution having diamonds particle dispersed therein, and method for producing the same
JP2011149071A
Surface-modified nanodiamond with controlled size
JP2012082103A
Method for forming composite plating film
JP2012092416A
Sliding member and method for producing the same
JP2013082956A